An ethnoveterinary survey of medicinal plants used in livestock ethnomedicine in selected communities in Makoni district, Zimbabwe - Jambwa, Prosper; Sithole, Ngonidzashe H.; Kasiyandima, Tatenda; Dzapasi, Vitalis; Mazadza, Allen; Mudimba, Toonse N; Gufe, Claudious (Ethnobotany Research and Applications, 2025)
Background: The application of ethnoveterinary medicine plays a vital role in the treatment of livestock in Zimbabwe despite the advent of contemporary medicine. However, documentation of this knowledge remains fragmented since ethnoveterinary surveys have not covered all the tribes in the country. Methods: An ethnoveterinary survey was carried out in Makoni district of Manicaland Province in Zimbabwe in order to document plants used in veterinary complementary medicine. Sixty questionnaire-based interviews were conducted in selected villages. The main areas of investigation were livestock health problems, livestock rearing and ethnobotanical expertise in animal health care. Frequencies of citations were obtained and informant consensus factors (Fic) for different health problems were calculated. Results: A total of twenty-six (26) plant species were recorded as being useful in the management of 13 categories of livestock health constraints in Mutanda and Domborembizi villages. The medicinal plants belonged to 20 families with the Fabaceae being the predominant family. The oral mode of administration had the highest percentage of citation (78.1%) followed by the topical method (17.3%) and application of medicinal plants to floors of poultry houses had the least citation (4.6%). All the animal health problems had informant consensus factors of greater than 0.9 except snake bites which had a very low Fic. Conclusion: The survey revealed that most farmers (83%) in the study area still relied on using ethnomedicine for the management of livestock health problems. The high Fic for most of the conditions shows that farmers agreed on plants used in the management of specific conditions. Aloe vera, Erythrina abyssinica, Melia azedarach and Pouzolzia mixta were the most cited plant species. Keywords: Ethnoveterinary, livestock, poultry, ruminant, traditional, conventional, plants